Le discours rapporté dans un corpus d’anglais oral : formes et frontières - Sylvie HANOTE (E-REA)
This paper investigates the intonational phrasing of reported speech clauses. It is based on the acoustic analysis of an oral corpus drawn from the radio (BBC Radio for British English and National Public Radio for American English) which has been compiled at Poitiers University. It contains about 8 hours of audio files (= ca 80,000 words) from various types of documents (political speeches, interviews, news broadcasts, scientific programmes…), most of them recorded from 2004 to 2013. The objective is to see whether there is a correlation between the “type” of the reported speech utterances (Direct / Indirect) and the prosodic behaviour of reporting and reported speech clauses in terms of prosodic integration or not of the reported speech clause in the reporting segment.